Perimortem caesarean section: Rethinking the resuscitation codes? - Deepak Mathur; Sng Ban Leong (Wolters Kluwer Medknow Publications, 2013)
Perimortem cesarean section is being recommended in pregnant women beyond 20-week gestation who are in extremis or cardiac arrest and in whom resuscitation appears to be failing. Aortocaval compression is removed by the delivery that promotes cardiac output in response to chest compressions. Feto-maternal outcome is thought to improve if the delivery is accomplished within 5 min of arrest. We describe the use of a public call announcement to minimize the time to delivery by bringing together a multidisciplinary team with the required equipment to the patients location and are able to perform a timely perimortem cesarean delivery if required, potentially improving the survival.